2012
DOI: 10.3171/2011.11.jns11530
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife surgery for skull base meningiomas

Abstract: Stereotactic radiosurgery offers a high rate of tumor control and neurological preservation in patients with skull base meningiomas. After radiosurgery, better outcomes were observed for those receiving an optimal radiosurgery dose and harboring tumors located in a cerebellopontine angle, parasellar, or petroclival location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 80 publications
5
92
1
7
Order By: Relevance
“…6 Some believe that skull-base tumors behave in a more benign fashion, 18 although others report late failures in this population. 5 Our patient series revealed that tumors in the skull base did not have significantly lower odds of treatment failure compared with non-skull base tumors (p = 0.35, local failure; p = 0.16, distant failure).…”
Section: Discussionmentioning
confidence: 99%
“…6 Some believe that skull-base tumors behave in a more benign fashion, 18 although others report late failures in this population. 5 Our patient series revealed that tumors in the skull base did not have significantly lower odds of treatment failure compared with non-skull base tumors (p = 0.35, local failure; p = 0.16, distant failure).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that these rates of tumor control are typically lower than those afforded by radiosurgery for meningiomas of the skull base. 23 The lower rates of tumor control may well be related to the vascular supply to these tumors and the possibility of recurrence at the margin of the treatment volume, particularly for those patients with prior resection. With radiosurgery in particular, the dural tail of a meningioma is not included in the planned treatment volume; many PSPF meningiomas do have an extensive dural tail.…”
Section: Radiosurgical Treatmentmentioning
confidence: 99%
“…In both cases, the agreement was parameterized by the gamma (γ) function, with a dose agreement of 3% and distance to agreement of 3 mm choosing an acceptance criteria of γ < 1 in more than the 93% of comparison points. 23 The Mean Delivery Time, defined as the approximate time needed in the LINAC "beam-on" phase, was investigated too. Correct patient setup was evaluated for each treatment session using the XVI CBCT and a 2 mm tolerance displacement level was considered acceptable.…”
Section: Rt Protocol:-mentioning
confidence: 99%